Current therapeutic approaches to haemostasis correction in covid-19: a systematic review - V. N. Antonov; M. V. Osikov; G. L. Ignatova; S. О. Zotov (Кубанский научный медицинский вестник, 2021)
Background. The coronavirus disease 2019 (COVID-19) caused by the SARS-CoV-2 virus has swept across countries worldwide. Despite an unprecedented volume of research, few drug therapies have been proved effective. The lack of evidence-based strategies entailed many practical treatments. Hypercoagulability observed in COVID-19 patients has sparked a debate in the medical community on therapeutic value of anticoagulants.Objectives. A review of up-to-date evidence supporting the therapeutic effect of unfractionated and low molecular-weight heparin as anticoagulant in treatment for COVID-19. Methods. Russian-language and foreign literature was mined in the RSCI, Scopus, PubMed, medRxiv and eLibrary databases for the years 2020–2021, with considering selected impactive publications within 1991–2019 as well. The query keywords were COVID-19, heparin [гепарин], hemostasis [гемостаз], thromboembolism [тромбоэмболия]. Peer-reviewed scientific journals received priority. Content and descriptive analytics were used as research tools.Results. The review surveyed 84 literature sources, with 51 articles selected for downstream analysis. We highlight usage of heparin and its fractions in treatment for COVID-19 and preclinical evidence verifying the antiviral and anti-inflammatory properties of heparin and synthetic heparin-like drugs in COVID-19. The known and plausible side effects demanding additional prospective randomised controlled trials on anticoagulant application in COVID-19 are reviewed, with an assessment of oral direct-acting anticoagulant drug efficiency.Conclusion. Drug-based therapies for haemostasis correction in COVID-19 are currently limited. The paucity of evidence warrants heparin usage as a safer therapy in acute COVID-19 compared to oral anticoagulants. However, the balance of its potential benefits vs. risks must be observed. The benefits and risk uncertainty in heparin treatment require randomised clinical trials and further studies to evaluate safety of direct-acting oral anticoagulants after the patient’s discharge in COVID-19.